2016
DOI: 10.1186/s12885-016-2979-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender difference on operative time in laparoscopic partial nephrectomy for T1 renal tumor and the utility of retroperitoneal fat thickness as a predictor of operative time

Abstract: BackgroundTo investigate the impact of biological gender on operative parameters, especially operative time, in laparoscopic partial nephrectomy (LPN) for T1 renal tumor.MethodsOne hundred and eleven (28 female and 83 male) patients and 64 (20 female and 44 male) patients with renal tumors suspected to be RCC cT1aN0M0 who underwent retroperitoneal and transperitoneal LPN, respectively, were analyzed. The influence of sex on operative factors including retroperitoneal fat tissue thickness, determined on CT, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…Further, our observation that operative time was also affected by the sex of the patients and the experience of surgeon concurs with results from previous reports. 22,23 On the other hand, there were no differences in the success rate of PTx between the RCMT and NCMT groups in the present study, probably because the anatomy of the parathyroid glands themselves, unlike the range or difficulty of dissection of parathyroid gland, was not affected by enlargement or pathological changes after treatment with calcimimetics. Conversely, enlargement of the parathyroid glands may even facilitate their detection during PTx.…”
Section: Discussioncontrasting
confidence: 60%
“…Further, our observation that operative time was also affected by the sex of the patients and the experience of surgeon concurs with results from previous reports. 22,23 On the other hand, there were no differences in the success rate of PTx between the RCMT and NCMT groups in the present study, probably because the anatomy of the parathyroid glands themselves, unlike the range or difficulty of dissection of parathyroid gland, was not affected by enlargement or pathological changes after treatment with calcimimetics. Conversely, enlargement of the parathyroid glands may even facilitate their detection during PTx.…”
Section: Discussioncontrasting
confidence: 60%
“…A recent retrospective study by Ito et al on 111 RCCs cT1aN0M0 [38] showed that males had a higher retroperitoneal fat tissue thickness (determined by computed tomography scan) than females, and that, as a consequence, the operative time during retroperitoneal laparoscopic NSS was significantly longer in male patients than in female patients (181.8 ± 34.9 min in males, 150.7 ± 24.7 min in females; p < 0.001). Overall, the operative time of retroperitoneal laparoscopic NSS was significantly correlated not only with gender, but also with maximum tumor diameter, and retroperitoneal fat tissue thickness.…”
Section: Surgery and Surgical Outcomesmentioning
confidence: 97%
“…Retroperitoneal fat thickness is reported to affect duration of surgery, as it did in the present study. In addition to male gender, Ito et al showed that retroperitoneal fat thickness is positively correlated with surgical duration 3 . In a prospective study of 100 robotic partial nephrectomies it was reported that surgery time in patients with APF was longer than in those without APF 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Patient-related factors, including gender, and visceral and perinephric fat thickness are clinically associated with the complexity of surgery and surgical outcome 1,3 . For predicting the complexity of perirenal fat dissection many researchers suggest using such tools as renal scoring systems and pre-operative computed tomography (CT) measurement 4,5 .…”
Section: Introductionmentioning
confidence: 99%